Treatment of cerebral vasospasm with self-expandable retrievable stents: proof of concept. (14th July 2016) - Bhogal, Pervinder; Loh, Yince; Brouwer, Patrick; Andersson, Tommy; Söderman, Michael
Abstract : Objective: To report our preliminary experience with the use of stent retrievers to cause vasodilation in patients with delayed cerebral vasospasm secondary to subarachnoid hemorrhage. Methods: Four patients from two different high volume neurointerventional centers developed cerebral vasospasm following subarachnoid hemorrhage. In addition to standard techniques for the treatment of cerebral vasospasm, we used commercially available stent retrievers (Solitaire and Capture stent retrievers) to treat the vasospastic segment including M2, M1, A2, and A1. We evaluated the safety of this technique, degree of vasodilation, and longevity of the effect. Results: Stent retrievers can be used to safely achieve cerebral vasodilation in the setting of delayed cerebral vasospasm. The effect is long-lasting (>24 hours) and, in our initial experience, carries a low morbidity. We have not experienced any complications using this technique although we have noted that the radial force was not sufficient to cause vasodilation in some instances. The vasospasm did not return in the vessel segments treated with stent angioplasty in any of these cases. In two of our cases stent angioplasty resulted in the reversal of focal neurological symptoms. Conclusions: Stent retrievers can provide long-lasting cerebral vasodilation in patients with delayed cerebral vasospasm.